Tectonic evolution of the Zagros foreland basin since Early Cretaceous, SW Iran: Regional tectonic implications from subsidence analysis. (December 2020) - Karimnejad Lalami, Hamid Reza; Hajialibeigi, Hossein; Sherkati, Shahram; Adabi, Mohammad Hossein
Graphical abstract: Highlights: Basement palaeo-highs exert major impact on the basin's subsidence history. Architecture of the Zagros foreland dramatically changed during the Cretaceous. NE-SW deep-seated basement faults were intensively re-activated during the Turonian. N-S deep seated basement faults were re-activated during the last 20 Ma. Abstract: Subsidence analysis of 42 exploration wells in the Zagros foreland basin indicates the tectonic evolution of the basin since Early Cretaceous. The impact of inherited basement structures on the basin evolution is documented in this study. Subsidence maps show that the architecture of the basin dramatically changed during the Cretaceous. In the Central Zagros, the Hercynian palaeo-high (i.e. Wadi Al Batin palaeo-high), which affected sedimentation until the Early Cretaceous time gradually disappeared and the South Pars palaeo-high within the central Persian Gulf started to show more impact on sedimentation. The palaeo-highs in the Zagros basement have different geometrical characteristics and origin. The Hercynian and South Pars are wide-wavelength palaeo-highs with a regional-scale impact on subsidence. In contrast, the Hendijan, Kharg-Mish and Kazerun palaeo-highs with different orientations and quite smaller wavelengths show different impact on the subsidence pattern. These kinds of palaeo-highs could be related to re-activation of pre-existing basement faults. Whereas South Pars and Hercynian paleo highs are possibly related to thermal expansion or contraction of the crust. The Hendijan and Kharg-Mish palaeo-highs with the NE-SW orientation were intensively re-activated during Turonian time. On the contrary, the Kazerun Fault with the N-S orientation became more active and considerably influenced sedimentation during the last 20 Ma. Selective re-activation of deep-seated faults might have taken place as a result of changes in the orientation of the far-field stress in the region. Understanding the complexities of inherited structures and their impact on reservoir characteristics can support future exploration activities in the Zagros foreland basin.